2005
DOI: 10.1103/physrevb.72.085131
|View full text |Cite
|
Sign up to set email alerts
|

Charge order induced by electron-lattice interaction inNaV2O5

Abstract: We present Density Matrix Renormalization Group calculations of the ground-state properties of quarter-filled ladders including static electron-lattice coupling. Isolated ladders and two coupled ladders are considered, with model parameters obtained from band-structure calculations for α ′ -NaV2O5. The relevant Holstein coupling to the lattice causes static out-of-plane lattice distortions, which appear concurrently with a charge-ordered state and which exhibit the same zigzag pattern observed in experiments. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 50 publications
1
21
1
Order By: Relevance
“…However, on an isolated ladder [7,8] the spin gap vanishes in the thermodynamic limit. The occurrence of the spin gap in NaV 2 O 5 appears to be intimately connected to the coupling of ladders, as indicated, e.g., by the splitting of magnon branches [4,12,13].…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…However, on an isolated ladder [7,8] the spin gap vanishes in the thermodynamic limit. The occurrence of the spin gap in NaV 2 O 5 appears to be intimately connected to the coupling of ladders, as indicated, e.g., by the splitting of magnon branches [4,12,13].…”
mentioning
confidence: 95%
“…In a recent DensityMatrix Renormalization Group (DMRG) study [8], we showed that the inclusion of a strong effective Holstein coupling to the lattice, which was found in local-density approximation (LDA) calculations [11], reduces the required Coulomb repulsion to a realistic value. The DMRG calculations then yielded good agreement between theoretical and experimental results for the amount of charge order, the extent of lattice distortion in the c direction, the effective spin coupling J eff in the b direction, and the charge gap.However, on an isolated ladder [7,8] the spin gap vanishes in the thermodynamic limit. The occurrence of the spin gap in NaV 2 O 5 appears to be intimately connected to the coupling of ladders, as indicated, e.g., by the splitting of magnon branches [4,12,13].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The "distracting" terms which are ignored are, [1], correlated hopping terms caused by the transformation which modify the t ij somewhat (Edegger 3 has estimated their effect in some detail); [2] phonon-mediated interactions, which to lowest order simply modify U, the remainder being small compared to J; [3] the longer-range coulomb interactions which play a role in the mesoscopic charge instabilities (like stripes) which are manifest for low doping and low temperatures, but don't affect the big picture. All can be included as extra terms in the projective Hamiltonian [3] (but must be projected).…”
Section: Formalismmentioning
confidence: 99%
“…Low-energy solutions of [3] are necessarily of the form ! " = P#(r 1 ,r 2 ,L,r N ), where # is a general function of all electron positions.…”
Section: Formalismmentioning
confidence: 99%